IgG subclass serum levels in juvenile chronic arthritis. Issue 5 (May 1986) - Martini, A; Plebani, A; Ravelli, A; Avanzini, M A; Jefferis, R; Zonta, L; Notarangelo, L D; Ugazio, A G; Burgio, R
Abstract : IgG subclass levels of sera from 26 patients with juvenile chronic arthritis (JCA) were determined by means of mouse monoclonal antibodies. Patients were divided into three groups according to clinical activity of the disease: active disease, partial remission, and remission. One hundred and sixty four age matched, healthy children served as controls. IgG subclass concentrations were log transformed, and a robust regression method was applied to obtain expected values for the different ages. We found a significant increase of IgG3 (p less than 0.0001), IgG1 (p less than 0.002), and IgG2 (p less than 0.035) in JCA sera, while IgG4 values did not differ significantly from those of controls. When patients were divided according to clinical activity significant increases of IgG2 and IgG4 were observed in the patients in partial remission. Our data suggest that differential increase of IgG subclasses during the courses of JCA may be of relevance to the pathogenesis of the disease.